Socio-economic and nutritional determinants associated with low birth weight among urban and rural Rajasthan: a case control study - Kabra, Mukesh; Dixit, Mukul; Verma, Anjana; Hirani, Jeetendra; Mathur, Medha (International Journal Of Community Medicine And Public Health, 2021)
Background: A baby’s weight at birth is associated with mortality risk during the first year, developmental problems in childhood and also with the risk of various diseases in adulthood. Methods: It was a hospital-based case control study conducted from 1st January 2019 to 30th June 2020 in a tertiary care hospital in Udaipur, Rajasthan. Mothers who delivered low birth weight baby (LBW) at the hospital, during the study period were taken as cases and controls were selected after matching. Total 86 cases and 172 controls were included in the study. A pre-structured questionnaire was used to collect information given by mothers. Results: Mean age was 28±4.51 years. Low birth weight was found to be significantly associated with sociodemographic variables such as rural area, caste and lower socio-economic status. Birth weight was also associated with weight gain during pregnancy, iron folic acid and calcium supplements and protein powder intake. Conclusions: Sociodemographic variables and maternal nutrition are the key determinants that need to be addressed to reduce the prevalence of LBW in India. Implementation of health promotion strategies are needed to address these factors effectively.